Aminiature on-board data recorder for unmanned latform - Dereń, Marcin (Advances in Mechanical and Materials Engineering, 2015)
The article presents the miniature CAN recorder. Thanks to its small dimensions, being easy to use and able to cooperate with programs such as Matlab, the recorder proves to be an universal and indispensable tool when examining devices in which the essential communication between elements is based on the CAN bus. The example of such a device is UAV platform. The article also provides a short description of the CAN bus and CANaerospace protocol.